Resistência insulínica por índice TyG: um estudo em agricultores do Espírito Santo - Ferreira, Júlia Rabelo Santos (2021)
INTRODUCTION: Rural populations have undergone changes inherent to work that affect their living and health conditions and increase the prevalence of cardiovascular diseases. The concomitant presence of overweight, hypertension, hyperglycemia and dyslipidemia constitute the Metabolic Syndrome, which is linked to Insulin Resistance. The gold standard method for determining IR is expensive and invasive, in this sense, the triglyceride/glucose (TyG) index was developed, which is less expensive and uses parameters that are routinely measured. Thus, the objective of this dissertation was to identify the cutoff point of the TyG Index according to components of MS and to estimate its prevalence and associated factors in rural workers in Espírito Santo. METHODS: This is a population-based cross-sectional study carried out with family farmers in the city of Santa Maria de Jetibá/ES. The TyG index was calculated from the equation: Ln [fasting triglycerides (mg/dL) x fasting glycemia (mg/dL)]/2, and MS was defined using the NCEP-ATPIII and IDF criteria. The cutoff values of TyG Index for MS were obtained using the Receiver Operating Characteristic (ROC) curve analysis with the area under the curve (AUC) and the Youden Index. RESULTS: The sample consisted of 790 individuals of which 52.3% were male (N=413), 29.2% had 31 to 40 years old (N=231), 67.5% had less than 4 years of study (N=533), 88.9% were white (n=702). The median TyG values were higher among individuals diagnosed with MS (p<0.001), and increased according to the aggregation of the components of MS. The TyG cutoff point was Ln 4.52, with a sensitivity of 82.96% and specificity of 76.76%. The prevalence of IR was 33.8% (N = 267). TyG was associated with age (p <0.001), body mass index (p <0.001) and schooling (p = 0.048). The age range of 31 to 40 years (OR = 1.723; 95% CI 1.02-2.89; p = 0.040), 41 to 50 years (OR = 3.357; 95% CI 1.95- 5.75; p <0.001) and over 50 years of age (OR = 2.535; 95% CI 1.43-4.48; p = 0.001), schooling (OR = 2.290; 95% CI 1.27-4.09; p = 0.005), smoking (OR = 1.859; 95% CI 1.01-3.93; p = 0.043) and being overweight (OR = 3.822; 95% CI 2.66-5.48; p <0.001) significantly increased the chance of presenting IR.